389 Impaired Coronary Endothelial Response to Exercise among Postpartum Women with Preeclampsia - Anum Minhas; Arthur Jason Vaught; Alborz Soleimani-Fard; Neal Fedarko; Maria Darla Esteban; Sammy Zakaria; Josef Coresh; Allison G. Hays (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Preeclampsia increases cardiovascular (CV) risk, likely via persistent endothelial dysfunction and angiotensin II type 1 receptor autoantibodies (AT1R-Ab). We aim to assess coronary endothelial function (CEF) and AT1R-Ab levels in postpartum preeclampsia with a hypothesis this mediates CV risk. METHODS/STUDY POPULATION: We prospectively enrolled age and CV risk factor matched postpartum women. Coronary MRI was performed at rest and with isometric handgrip stress, an endothelial dependent stressor. CEF was quantified as % stress-induced change in coronary cross-sectional area (%CSA) and in coronary blood flow (%CBF). AT1R-Ab was measured using a novel antigen capture enzyme-linked immunosorbent assay. RESULTS/ANTICIPATED RESULTS: Women with and without preeclampsia were similar in age (mean 32.7+5.0 years), BMI (mean 28.0+6.3 kg/m2) and race/ethnicity (58% White, 35% Black and 4% Hispanic). %CSA was lower with (-2.1+13.6) vs without preeclampsia (8.8+17.1), p=0.023. %CBF was also lower with (11.3 [-11.8, 25.2]) vs without preeclampsia (25.7 [-0.7, 62.9]), p=0.039. AT1R-Ab was higher among women with preeclampsia (p=0.029) and was inversely associated with %CBF (beta coefficient -4.6 [-8.9, -0.3], p=0.037) but not with %CSA. DISCUSSION/SIGNIFICANCE: Women with preeclampsia have elevated AT1R-Ab and impaired CEF demonstrated by insufficient coronary reserve with exercise. Coronary endothelial dysfunction and dysregulation of the renin-angiotensin pathway likely contribute to long-term CV risk and should be considered for targeted risk reduction.